ANALISIS KANDUNGAN ANGKA LEMPENG TOTAL DAN Escherichia coli PADA IKAN NILA DAN MUJAIR DI UNIT PENGOLAHAN AIR LIMBAH (UPAL) PT. INDONESIA TOURISM DEVELOPMENT CORPORATION - Azizah Diniari, Nur; Dewi Anggreni, Anak Agung Made; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
This research aims to know the influence of the type of fish and the pool location on the content of Total Plate Count and Escherichia coli in Nile tilapia and Mozambique tilapia maintained by Wastewater Treatment Unit of Indonesia Tourism Development Corporation and to determine the content of Total Plate Count and Escherichia coli in Nile tilapia and Mozambique tilapia maintained by Wastewater Treatment Unit of ITDC. This study used a randomized block design factorial. The first factor was the type of fish which consists of two type i.e. Nile tilapia and Mozambique tilapia. The second factor was location of the pool consisting of two location were 2B pool and 3 pool. From these factors obtained four treatment combinations which were grouped into 4 time-based sampling in order to obtain 16 experimental units. Data were analyzed with analysis of variance followed by Least Significant Difference when a significant effect of treatment. The results of this study showed that types of fish, pool location and interaction between treatments had not significant with the content of total plate count, and Escherichia coli. Range of total plate count on Nile tilapia and Mozambique tilapia in 2B pool and 3 pool was 11.9 x10 11 CFU/g to 17.9 x10 11 CFU/g, and the content of Escherichia coli were negative.
Keywords: 47